Cost-effectiveness of ticagrelor versus clopidogrel in patients with acute coronary syndromes in Canada - Grima DT; Brown ST; Kamboj L; Bainey KR; Goeree R; Oh P; Ramanathan K; Goodman SG (Dove Medical Press, 2014)
Daniel T Grima1, Stephen T Brown1, Laveena Kamboj2, Kevin R Bainey3, Ron Goeree4,5, Paul Oh6, Krishnan Ramanathan7, Shaun G Goodman81Cornerstone Research Group, Burlington, ON, 2AstraZeneca Canada, Mississauga, ON, 3Mazankowski Alberta Heart Institute/University of Alberta Hospital, Edmonton, AB, 4Program for Assessment of Technology in Health, St Joseph's Hospital, Hamilton, ON, 5Department of Clinical Epidemiology and Biostatistics, McMaster University, Hamilton, ON, 6University Health Network, Toronto, ON, 7St Paul's Hospital, Vancouver, BC, 8St Michael's Hospital, University of Toronto, Toronto, ON, CanadaBackground: Ticagrelor demonstrated a significant reduction in major cardiac events in patients with acute coronary syndrome (ACS) compared with clopidogrel in the Platelet Inhibition and Patient Outcomes (PLATO) trial. The objective of this study was to assess the cost-effectiveness of ticagrelor compared with clopidogrel in ACS patients from the perspective of the Canadian publicly funded health care system.Methods: A two-part model was developed consisting of a 1-year decision tree and a lifetime Markov model. Within the decision tree, patients remained event-free, experienced a nonfatal myocardial infarction, a nonfatal stroke, or death due to vascular or nonvascular related causes based on data from the PLATO trial. The lifetime Markov model followed these patients and allowed for subsequent myocardial infarction, stroke, and death. Patient utility and resource use were derived from the PLATO trial. Transition probabilities and specific Canadian unit costs were derived from published sources. Univariate and probabilistic sensitivity analyses were conducted.Results: In the base case lifetime analysis, treatment with ticagrelor resulted in more years of life per person (0.097), more quality-adjusted life years per person (QALYs, 0.084), and an incremental cost per QALY gained of $9,745 (Canadian$), assuming a generic cost for clopidogrel. A probabilistic sensitivity analysis demonstrated the robustness of the base case analysis, with a 93% probability of being below $20,000 per QALY gained and a 99% probability of being below $30,000 per QALY gained.Conclusion: Ticagrelor is a clinically superior and cost-effective option for the prevention of thrombotic events among ACS patients in Canada.Keywords: acute coronary syndrome, percutaneous coronary intervention, cost-effectiveness analysis, cost-utility analysis, clopidogrel, ticagrelor, antiplatelet therapy